Answer:
[tex]\csc(30\degree)[/tex]
Step-by-step explanation:
The given trigonometric expression is
[tex]\csc(-330\degree)[/tex]
Recall that;
[tex]\csc(\theta)=\frac{1}{\sin(\theta)}[/tex]
This implies that;
[tex]\csc(-330\degree)=\frac{1}{\sin(-330)}[/tex]
Recall again that;
[tex]\sin(-\theta)=-\sin(\theta)[/tex]
We apply this property to get;
[tex]\csc(-330\degree)=-\frac{1}{\sin(330)}[/tex]
Finally, we apply the following property of the sine function to get;
[tex]\sin(360\degree-\theta)=-\sin(\theta)[/tex]
[tex]\csc(-330\degree)=-\frac{1}{\sin(360\degree-30\degree)}[/tex]
[tex]\csc(-330\degree)=-\frac{1}{-\sin(30\degree)}[/tex]
[tex]\Rightarrow \csc(-330\degree)=\frac{1}{\sin(30\degree)}[/tex]
We rewrite using reciprocal ratios to get;
[tex]\Rightarrow \csc(-330\degree)=\csc(30)[/tex]